THE EFFECT OF PRODUCT QUALITY ON CONSUMER BUYING INTEREST WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE BLACK MARKET TEBING TINGGI ONLINE STORE - Handayani Harahap, Hastuti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine how the influence of product quality on consumer buying interest with customer satisfaction as an intervening variable at the Tebing Tinggi Black Market Online Store. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of product quality variables on consumer buying interest using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of testing the first hypothesis are accepted, meaning Product Quality(X) has a positive and significant effecton Customer Satisfaction (Z). The second hypothesis is accepted, meaning that the product quality (X) has a positive and significant effectto Purchase Interest (Y). The third hypothesis is accepted, meaning Customer Satisfaction (Z)take effectpositive andsignificantto Purchase Interest (Y). Path analysis shows the direct effect of variable X on variable Y of 0.670. Meanwhile, the indirect effect through variable Z is 0.803 x 0.273 = 0.2192. From the calculation results obtained, it shows that the direct effect through variable X is greater than the indirect effect on variable Y.